Discovery and in vitro characterization of a human anti-CD36 scFv - Mata-Cruz, Cecilia; Guerrero-Rodríguez, Sandra L.; Gómez-Castellano, Keyla; Carballo-Uicab, Gregorio; Almagro, Juan Carlos; Pérez-Tapia, S. Mayra; Velasco-Velázquez, Marco A. (Frontiers in Immunology, 2025)
IntroductionCD36 is a membrane receptor that participates in the cellular uptake of fatty acids and lipid metabolism. CD36 overexpression favors progression of different pathologies, such as atherosclerosis and cancer. Thus, CD36 targeting has medicinal relevance. Herein, we aimed to identify human anti-CD36 single-chain variable fragment (scFv) with therapeutic potential.MethodsThe semisynthetic ALTHEA Gold Plus Libraries™ were panned using recombinant human CD36. Clone selection was performed by ELISA. Analysis of scFv binding and blocking function was evaluated by flow cytometry in macrophage-like THP-1 cells and hepatocellular carcinoma HepG2 cells. The phenotypic changes induced by CD36 ligands were assessed in vitro by: i) oil red staining, ii) tumorsphere assays, and iii) RT-qPCR.ResultsWe identified an anti-CD36 scFv, called D11, that competes with a commercial anti-CD36 antibody with proven efficacy in disease models. D11 binds to CD36 expressed in the membrane of the cellular models employed and reduces the uptake of CD36 ligands. In macrophage-like THP-1 cells, D11 impaired the acquisition of foam cell phenotype induced by oxLDL, decreasing lipid droplet content and the expression of lipid metabolism genes. Treatment of HepG2 cells with D11 reduced lipid accumulation and the enhanced clonogenicity stimulated by palmitate.ConclusionWe discovered a new fully human scFv that is an effective blocker of CD36. Since D11 reduces the acquisition of pathogenic features induced by CD36 ligands, it could support the generation of therapeutic proteins targeting CD36.